Artemia salina: A microcrustacean to assess engineered nanoparticles toxicity. Issue 3 (28th September 2020) - Pecoraro, Roberta; Scalisi, Elena Maria; Messina, Giuseppina; Fragalà, Giuseppe; Ignoto, Sara; Salvaggio, Antonio; Zimbone, Massimo; Impellizzeri, Giuliana; Brundo, Maria Violetta
Abstract: The focus of this work was to investigate the toxicity of different metal nanoparticles (gold nanoparticles [AuNPs], silver nanoparticles [AgNPs], titanium dioxide nanoparticles [TiO2 NPs]) on brine shrimp Artemia salina . We investigated if nanoparticles could have an influence on hatching of cysts and on mortality of larvae. Larvae (also called nauplii) and cysts were exposed to NPs for 24 hr in artificial seawater on microplates. At the end of the test, we assessed the endpoint (immobility/death) for the larvae by a stereomicroscope. Nauplii that appeared completely motionless, were counted as dead, and the percentages of mortality were calculated for each treatment. Instead for the cysts, the percentages of not‐hatched nauplii for each concentration considered were calculated by counting the number of whole cysts. Currently, nanoparticles toxicity has been investigated in several research; in our study we highlighted the nontoxicity of TiO2 NPs on A. salina nauplii as shown by low percentages of immobilization and on cysts because TiO2 NPs do not affect their hatching. Despite AuNPs exerted toxic effects on hatching, they did not affect larvae development as well as TiO2 NPs. Otherwise, AgNPs induced mortality of the larvae and inhibited cysts hatching. Abstract : This study evaluates the toxicity of different metal nanoparticles on a microcrustacean. Silver nanoparticles are more toxic on larvae than gold and titanium dioxide nanoparticles, and influence hatching cysts. Artemia salina can be employable in toxicity assessment of engineered nanomaterials.